The Social Behaviors of Marginal Group Adolescents in Semarang - Sumihudiningsih, Yekti; Soesilowati, Etty; Tri Atmaja, Hamdan (JESS (Journal of Educational Social Studies), 2019)
Marginal people become a problem in Semarang. Kemijen is a village or a village in East Semarang Regency. It is a place for marginal people in Semarang. Kemijen has both physical and social environment problems. Indeed, this location is not suitable to stay either for adults, adolescents, or children. One of the concerning matters deals with adolescents. The adolescent phase remains in an important individual development stage. This research aims to analyze the role of the area, habitus, and social capital for adolescents of marginal people and their social behaviors in Semarang. This qualitative research collected the data from a deep interview, observation, and literature study. The data analysis used data reduction, presentation, and conclusion stages. The findings showed the area, habitus, and social capital influenced the dropout-adolescents’ social behaviors. Meanwhile, the school arena of the adolescents’ residences and the social capital did not influence the adolescents’ social behaviors at schools. The social behaviors of the marginal people in Semarang consisted of politeness, lifestyle, peer-interaction, the opposite sex interaction, and life perspective. The adolescents’ social behaviors of the marginal people were grouped into two. Dropout adolescents' social behaviors tended to be negative. Meanwhile, the adolescents that still went to schools tended to be positive.